KEBERAGAMAAN MAHASISWA DI PERGURUAN TINGGI WILAYAH MINORITAS MUSLIM - Wekke, Ismail Suardi; Hermawanto, Asep; Ashrori, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Higher education is a part of society, therefore Islamic university also as part of their environment. This article would identify how Islamic higher education accelerates their institution to give students any opportunity to learn religious subject outside classroom. They have enough time to learn in non-formal situation. Data was collected through the brief in-depth interview and non-participant observation. Islamic State College of Sorong is the main source of data. Focus group discussion was the technique to verify data for triangulation. This article discusses two main activity, they are a celebration of Prophet Muhammad and the moment of first time reciting Quran. Finally, this article concludes that the institution in higher learning activity play two roles, the university itself, and the same time they are the religious body of the society.